2021
DOI: 10.3390/cells10081979
|View full text |Cite
|
Sign up to set email alerts
|

From Microspikes to Stress Fibers: Actin Remodeling in Breast Acini Drives Myosin II-Mediated Basement Membrane Invasion

Abstract: The cellular mechanisms of basement membrane (BM) invasion remain poorly understood. We investigated the invasion-promoting mechanisms of actin cytoskeleton reorganization in BM-covered MCF10A breast acini. High-resolution confocal microscopy has characterized actin cell protrusion formation and function in response to tumor-resembling ECM stiffness and soluble EGF stimulation. Traction force microscopy quantified the mechanical BM stresses that invasion-triggered acini exerted on the BM–ECM interface. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
4
10
0
Order By: Relevance
“…On day 4 of development, spheroids appeared poorly developed with unorganized cell clusters and thin BM scaffold. This thin BM was frequently penetrated by actin protrusions ( Figure 5A' , white arrows), as reported previously ( Eschenbruch et al, 2021 ). Basoapical cell polarization was reached partially at day 11 and fully at day 18, at which partial lumen clearance was regularly observed.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…On day 4 of development, spheroids appeared poorly developed with unorganized cell clusters and thin BM scaffold. This thin BM was frequently penetrated by actin protrusions ( Figure 5A' , white arrows), as reported previously ( Eschenbruch et al, 2021 ). Basoapical cell polarization was reached partially at day 11 and fully at day 18, at which partial lumen clearance was regularly observed.…”
Section: Resultssupporting
confidence: 85%
“…We found that the basal cell layer of spheroids at day 3–4 formed short actin microspikes penetrating the thin BM. Moreover, it was shown that these ECM probing microspikes form focal adhesions to the BM and the ECM, especially in the early developmental stages of spheroids with low polarization ( Eschenbruch et al, 2021 ). Considering actin-rich protrusions as the prevailing mechanism for ECM-mechanosensation, we hypothesize a shear strain-induced opening of PIEZO-1 ion channels as one of the primary sensing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Invadosomes also have a dynamic life cycle [ 282 ]. Cells of breast acini probe the ECM with non-proteolytic actin microspikes, which, as functional precursors of invadopodia, widen pores in the collagen IV meshwork with force-transmitting focal adhesions and initiate BM penetration [ 372 ]. In cells disseminating into the ECM, such non-proteolytic microspikes are then converted into proteolytically active invadopodia containing MMP-14 [ 372 ].…”
Section: Cellular Adhesome Structures In the Tmementioning
confidence: 99%
“…Cells of breast acini probe the ECM with non-proteolytic actin microspikes, which, as functional precursors of invadopodia, widen pores in the collagen IV meshwork with force-transmitting focal adhesions and initiate BM penetration [ 372 ]. In cells disseminating into the ECM, such non-proteolytic microspikes are then converted into proteolytically active invadopodia containing MMP-14 [ 372 ]. The formation of invadopodia is stimulated by ECM rigidity, degradation of ECM molecules, and growth factor signaling [ 361 , 373 , 374 , 375 , 376 , 377 ].…”
Section: Cellular Adhesome Structures In the Tmementioning
confidence: 99%
“…19 These results agreed with previous observations that more actin-rich protrusions from cell edges generated larger contractile forces during cell migration. 49…”
Section: Cell Traction Force Exerted On Microposts With Nanopillars O...mentioning
confidence: 99%